Reduced Binding of the Endolysin LysTP712 to Lactococcus lactis ΔftsH Contributes to Phage Resistance - Roces, Clara; Campelo, Ana B.; Escobedo, Susana; Wegmann, Udo; García, Pilar; Rodríguez, Ana; Martínez, Beatriz (Frontiers in Microbiology, 2016)
Absence of the membrane protease FtsH in Lactococcus lactis hinders release of the bacteriophage TP712. In this work we have analysed the mechanism responsible for the non-lytic phenotype of L. lactis ΔftsH after phage infection. The lytic cassette of TP712 contains a putative antiholin-pinholin system and a modular endolysin (LysTP712). Inducible expression of the holin gene demonstrated the presence of a dual start motif which is functional in both wildtype and L. lactis ΔftsH cells. Moreover, simulating holin activity with ionophores accelerated lysis of wildtype cells but not L. lactis ΔftsH cells, suggesting inhibition of the endolysin rather than a role of FtsH in holin activation. However, zymograms revealed the synthesis of an active endolysin in both wildtype and L. lactis ΔftsH TP712 lysogens. A reporter protein was generated by fusing the cell wall binding domain of LysTP712 to the fluorescent mCherry protein. Binding of this reporter protein took place at the septa of both wildtype and L. lactis ΔftsH cells as shown by fluorescence microscopy. Nonetheless, fluorescence spectroscopy demonstrated that mutant cells bound 40 % less protein. In conclusion, the non-lytic phenotype of L. lactis ΔftsH is not due to direct action of the FtsH protease on the phage lytic proteins but rather to a putative function of FtsH in modulating the architecture of the L. lactis cell envelope that contributes to a lower affinity of the phage endolysin to its substrate and, likely to its catalytic activity.